ACOUSTIC ENERGY AT CHANGE OF TREATED COMPOSITE MATERIAL DISPERSION PROPERTIES - Filonenko, Sergii (Proceedings of National Aviation University (archive), 2016)
Purpose: The aim of this study is to investigate the influence of treated composite material dispersion properties on acoustic radiation energy, which appears during composite material machining. Methods: The researches were grounded on simulation of acoustic radiation energy at change of mechanically treated composite material properties dispersion for the mechanical model of its surface layer destruction. The data processing with definition of acoustic radiation statistical energy parameters was conducted. The analysis of acoustic emission energy parameters sensitivity to change of composite material properties dispersion, and as the analysis of influencing of composite material properties dispersion on AE amplitude and energy parameters was conducted. Results: Were obtained that at decreasing of composite material properties dispersion there is increasing an average level of acoustic radiation energy and value of its deviation. Is determined, that at decreasing of composite material properties dispersion the greatest increasing there is an acoustic emission energy average level dispersion. It is show that the increasing of acoustic radiation energy parameters advances increasing its amplitude parameters. Discussion: The simulation of acoustic radiation energy at composite material machining for the mechanical model surface layer destruction at decreasing of composite material properties dispersion (spread) is conducted. It is shown, that the decreasing of composite material properties dispersion does not influence on acoustic radiation energy nature change. At the same time, the ascending parameter, that describing of composite material properties dispersion decreasing, results in increase of acoustic radiation signal energy parameters. The obtained outcomes can be used at mining methods of verification, diagnostic and monitoring of composite material machining technological processes. Thus during the composite material machining is possible to control and to determine of composite material properties rejection by analysis of acoustic emission signal energy average level dispersion.